Individualized approach to infertility management with dydrogesterone: insights from case series - Tambe, Pratik; Khalse, Maneesha; Patel, Kamlesh; Parekar, Reshma (Indian Journal of Case Reports, 2025)
Infertility is a growing global concern, affecting about one in six individuals of reproductive age. In India, reported prevalence ranges from 3.9% to 16.8%, influenced by age, infections, lifestyle factors, and sociocultural elements. This case series highlights six women, aged 30–34 years, each presenting with different infertility challenges: Tubal factor infertility, male factor infertility, recurrent pregnancy loss, unexplained infertility, and early-stage endometriosis. All cases were managed with a personalized treatment approach that included oral dydrogesterone for luteal phase support (LPS). Dydrogesterone, a selective oral progestin with high bioavailability and endometrial specificity, was used to improve luteal phase adequacy and endometrial receptivity. Each patient received tailored care involving either natural conception support, ovulation induction, intrauterine insemination, or assisted reproductive technology, depending on their clinical profile. Oral dydrogesterone was administered as part of LPS in all six cases. Outcomes included successful conception or sustained pregnancy, demonstrating clinical benefit in each scenario. These real-world clinical cases emphasize the importance of individualized infertility management and illustrate the versatile role of dydrogesterone across varied reproductive conditions. Its incorporation into treatment protocols supported favorable outcomes, reinforcing its value in both spontaneous and assisted conception pathways.